Itogi . Itogi . Results . Итоги - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Military actions in Tajikistan; murder of the Vice-Head of Russian Government Viktor Polianichko; political crisis in Georgia; celebration of the 50th anniversary of the Battle of Kursk; extended meeting of the Russian Government; meeting of the Supreme Council of Russia. Featured in the program: Nazarbaev, Nursultan Abishevich (President of Kazakhstan); Chubais, Anatolii Borisovich (People's Deputy of the Russian Federation); Shakhrai, Sergei Mikhailovich (Vice Prime Minister of the Russian Government); Chernomyrdin, Viktor Stepanovich (Prime Minister of the Russian Federation) Contributors: Kiselev, Evgenii (Anchor) Военные действия в Таджикистане; убийство заместителя председателя Правительства России Виктора Поляничко; политический кризис в Грузии; празднование пятидесятилетия Битвы на Курской Дуге; расширенное заседание Правительства России; заседание Верховного Совета Российской Федерации. В программе участвуют: Назарбаев, Нурсултан Абишевич (Президент Казахстана); Чубайс, Анатолий Борисович (Народный депутат Российской Федерации); Шахрай, Сергей Михайлович (Вице-премьер правительства России); Черномырдин, Виктор Степанович (Председатель правительства Российской Федерации) Создатели: Киселев, Евгений (Ведущий/Ведущая)